Invisible caregivers : older adults raising children in the wake of HIV/AIDS - Joslin, Daphne (Columbia University Press, 2002)
An understudied aspect of the HIV/AIDS epidemic is the creation of hundreds of thousands of grandparent-headed households that have become home to children bereft of one or both of their parents. Such "skip-generation parenting" presents a host of challenges to the families involved and the social programs designed to assist them. Despite this unprecedented caregiving responsibility, older surrogate parents remain relatively invisible, hidden in the shadows of HIV care and the demands of raising a child. The primary goal of Invisible Caregivers is to generate, support, and guide program and policy initiatives designed to meet the needs of elder surrogates and their families. Most social service programs are not able to identify the needs of older surrogates, often because these surrogate parents in HIV-infected families are reluctant to make their needs known for fear of social stigma or possible reductions of benefits. Multiple systemic barriers to case management and other services also frustrate attempts to bring available resources to elder caregivers. These barriers include professional ignorance or denial that HIV affects surrogates, eligibility restrictions through CARE, limited funding and age restriction on OAA, and a fragmented health and human service system. Because the issues facing elder caregivers are many and varied, this collection covers a host of issues: community health, aging, HIV services, child welfare, education, public policy, and mental health